A new IoT resource addressing method based on rough set neural network. (15th March 2023) - Jin, Liang; Li, Wei; Meng, Qinghui
In order to overcome the problems of low precision and long time in traditional resource addressing methods of Internet of Things (IoT), this paper proposes a new resource addressing method based on rough set neural network, which enhances the information processing ability of rough set neural network and establishes a new decision system modelling method. The resource names are refined into original resource names and transformed resource names through the model. At the same time, the resource addresses are expanded into resource address information with standard hierarchical structure information and expanded hierarchical structure information, which provides important information for the transformation of resource names and realises the IoT resources addressing. The experimental results show that the proposed method can effectively improve the addressing accuracy and reduce the average search time, and the node failure problem is significantly improved.